2021
DOI: 10.1111/apa.15737
|View full text |Cite
|
Sign up to set email alerts
|

Utility of lung ultrasound and respiratory severity score for detection of respiratory distress syndrome in the delivery room

Abstract: Utility of lung ultrasound and respiratory severity score for detection of respiratory distress syndrome in the delivery room.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
1
0
Order By: Relevance
“…Therefore, bedside lung ultrasound can be used as a portable, easy-to-operate, safe, non-invasive and repeatable examination method. Some foreign scholars have found that the sensitivity of lung ultrasound in the diagnosis of neonatal atelectasis is 100%, which is significantly higher than 70% of X-ray examination, confirming the diagnostic value of lung ultrasound in neonatal lung diseases [ 18 ]. The results of this study showed that the lung ultrasound score had high clinical value in the differential diagnosis of NRDS neonates and common lung diseases, as well as the severity of NRDS.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, bedside lung ultrasound can be used as a portable, easy-to-operate, safe, non-invasive and repeatable examination method. Some foreign scholars have found that the sensitivity of lung ultrasound in the diagnosis of neonatal atelectasis is 100%, which is significantly higher than 70% of X-ray examination, confirming the diagnostic value of lung ultrasound in neonatal lung diseases [ 18 ]. The results of this study showed that the lung ultrasound score had high clinical value in the differential diagnosis of NRDS neonates and common lung diseases, as well as the severity of NRDS.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these data, we consider that LUS could be used as an aid to establish the need for respiratory support in the delivery room. Indeed, even if there have been discussions about the superiority of a clinical score in the delivery room to establish the need for positive pressure and surfactant administration [ 43 ]—considered better than LUS because LUS needs a new device to be operated in the delivery room, needs a trained person, and needs more time spent in evaluation—LUS is a more objective parameter, is consistent, comes with a good predictive value as demonstrated by other studies both in the delivery room [ 24 , 31 ] and during the first hours of life [ 6 , 33 , 34 , 44 ], could result in earlier respiratory support and surfactant administration [ 44 ], and could improve the prognosis of the neonates. Maintaining a good respiratory status in premature neonates could also result in improved general homeostasis and the avoidance of important neurologic complications [ 45 ].…”
Section: Discussionmentioning
confidence: 99%